Investigations on cocoa by-products with a special emphasis on the cocoa fruit pulp - Bickel Haase, Thomas; Justus Liebig University Giessen (My University, 2024)
This dissertation explores valorisation technologies for using cocoa fruit pulp and cocoa pod husks as food ingredients. Chapter 1 examined the aroma composition of fresh pulp from four countries of origin, identifying a wide range of aroma-active substances with qualitative variations across different pulps. Pasteurization and ultra-high temperature treatment were studied in Chapter 2 to prolong the shelf-life of cocoa pulp while aiming to maintain its sensory attributes. Enzyme-assisted hydrolyses were investigated in Chapter 3 for cocoa pulp processing, focusing on the influence of temperature, enzyme activity, and enzyme combinations on different physicochemical parameters. In Chapter 4, the fermentation of cocoa pod husks by Pleurotus salmoneo-stramineus was delved into to produce a protein- and fibre-rich ingredient, thereby focusing on its techno-functional properties. This dissertation provides valuable knowledge for optimising the utilization of cocoa by-products for food applications and promoting more sustainable practices in the cocoa supply chain.
Keywords: Cocoa by-products; Fruit pulp; Cocoa pod husks; AEDA; ddc:540